EFFORTS TO IMPROVE KINESTHETIC INTELLIGENCE IN CHILDREN AGED 5-6 YEARS THROUGH TRADITIONAL DANCE ACTIVITIES BANYUWANGI AT PGRI BEDEWANG KINDERGARTEN, SONGGON DISTRICT, BANYUWANGI REGENCY - Luluk, Fitriyani; Ianatuz, Zahro; Trio, Suwargono (Journal of Education Technology and Inovation, 2024)
This research aims to improve the kinesthetic intelligence of children aged 5-6 years through traditional Banyuwangi dance activities. The method used is Classroom Action Research (PTK) which consists of two cycles, with each cycle involving two meetings. Data was analyzed using quantitative and qualitative approaches. The results showed that at the pre-cycle stage, of the 16 children studied, 13 children were in the not yet developing category, and 3 children were in the beginning to develop category (18.75%). After taking action through Banyuwangi traditional dance activities in cycle I, there was an increase, where 7 children had developed according to expectations (43.75%), while 6 children were still in the starting to develop category, and 3 children were still not developing. In cycle II, a significant increase occurred, with 13 children developing according to expectations and 3 children in the beginning to develop category (81.25%). This research shows that Banyuwangi traditional dance activities are effective in improving the kinesthetic intelligence of children aged 5-6 years at PGRI Bedewang Kindergarten